Legal Problems and Challenges of Indonesian Personal Data Protection of Children and Persons with Disabilities in Society 5.0 - Cahyaning Putri, Cyndiarnis; Ganindha, Ranitya; Sihabudin (The Center for Disability Studies and Services Brawijaya University, 2025)
In the era of society 5.0, high percentage of internet penetration in Indonesia also poses one of the risks, namely related to the misuse of children and person with disabilities's privacy and personal data. Protection of children and person with disabilities's personal data in Indonesia is an urgency that needs to be immediately accommodated in Indonesia regulations. Unfortunately, according the existing regulations, the protection of children's personal data is only found in the Indonesia Personal Data Protection Law and merely regulated in three articles. The problems and challenges in providing legal protection for children and person with disabilities's personal data in Indonesia are in the need for regulations which comprehensively regulate the protection of children's personal data. The Indonesia Personal Data Protection Law can be amended by also including three points, namely: the meaning of special processing, parental and guardian consent, and limitations on the processing of children's personal data.